Pengaruh kadar karbon pada material logam mampu luruh Fe-35Mn-C hasil metalurgi serbuk dengan kalium karbonat sebagai agent pembuat foam - Yudha Pratesa; Setyaningrum (MBI, 2024)
: A Fe-35Mn-1C alloy with a foam structure, incorporating 5% potassium carbonate (K2CO3), was successfully synthesized, demonstrating an austenite phase and an acceptable degradation rate for an implant candidate. However, excessive carbon content led to the formation of a graphite phase and increasing hardness. To address this, variations in lower carbon composition (0% and 0.5%) were explored to enhance mechanical properties and achieve a fully austenite phase with non-magnetic properties. Mechanical alloying of the powder materials was performed using the rotary mixing method and was followed by sintering process in argon atmopher. The sintered samples underwent comprehensive characterization, including physical, chemical, mechanical properties, and degradation behavior. The Fe-Mn-C biomaterial exhibited an austenite and manganese oxide phase with a favorable degradation rate. This study showed K2CO3 is not only as a foaming agent but also could contribute to carbon alloying into the Fe-Mn alloy system.